ANALISIS TUMPANG TINDIH REGULASI DALAM PENETAPAN AREA KEWENANGAN IMIGRASI DI WILAYAH PERBATASAN INDONESIA: ANALYSIS FOR THE OVERLAPPING REGULATIONS IN DETERMINING IMMIGRATION AUTHORITY AREAS IN INDONESIA BORDERS - Parulian, Sandy Christian; Ryanindityo, Mochamad; Widayat, Wisnu (Journal of Administration and International Development, 2025)
The management of immigration authority in Indonesia's border areas faces significant challenges due to overlapping regulations among government agencies, which undermines the effectiveness of surveillance and law enforcement. The urgency of this issue lies in the need for integrated policies to safeguard national sovereignty and security. This study aims to analyze the causes, impacts, and potential solutions to regulatory overlaps in defining immigration jurisdiction in border regions. A qualitative research method was employed, using a case study approach involving in-depth interviews with key informants, document analysis, and thematic analysis based on Edwards III’s policy implementation theory. The findings reveal regulatory disharmony, weak institutional coordination, and limited resources that hinder the effective implementation of immigration policies. This study contributes to the literature on border governance by emphasizing the necessity for regulatory harmonization and cross-sectoral synergy. It concludes that responsive and adaptive policy reform is essential to strengthen Indonesia’s national immigration system. Future research is recommended to broaden the geographical scope and apply a multidisciplinary approach to capture the complexity of border governance more comprehensively.